STRATEGI KOMUNIKASI PEMASARAN BADAN URUSAN LOGISTIK (BULOG) DIVRE RIAU-KEPRI DALAM PENJUALAN BERAS KOMERSIL DI PEKANBARU - Juliandini, Adista; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
There are still many people who do not know that Bulog also has a commercial function. So there are some people who think commercial rice sold is raskin. This researchers obtained from the results of simple interviews from the community in some circles regarding Bulog commercial rice. There are still people who do not know that Bulog commercial rice has a different quality than raskin rice. Commercial rice has a premium quality while medium-quality raskin rice. So rice that is distributed with commercial rice has a different quality. In the case of commercial rice the quality is no less competitive with existing partner rice brands and the price is cheaper.The researcher uses qualitative descriptive method where the researcher do observation and depth interview and acts as facilitator, reality will be constructed by research subjects so that it occurs naturally (natural setting), Primary data in this research is obtained from observation at Riau Bulri divre-Riau Islands, interviews to employees, or documentation during the study.Based on the results of observations and interviews of authors in the field, direct marketing is done by Bulog Divre Riau-Kepri in the sale of commercial rice. Bulog created a breakthrough to supply the food needs of the community. Bulog makes our Food House (RPK), to sell the basic necessities of society at affordable prices Direct Marketing Bulog also contacts consumers directly using the phone and Bulog also directly come to the place of its customers. Marketing communication strategy in the form of public relations done by Bulog Divre Riau-Kepri in selling commercial rice in Pekanbaru is by doing OP activity (market operation) which is one marketing communication strategy to reach wider society, marketing communication strategy in Word of Mouth form of Bulog Divre Riau-Riau Islands in the sale of commercial rice in Pekanbaru is Bulog started from tools that can be used that is banners placed in front of the office and Bulog Divre Riau-Riau. Bulog also started their communication from nearby people and relatives to provide information on commercial rice.Keyword: Marketing Communication Strategy, Direct Marketing, Public Relation, Word of Mouth